In vitro catharanthus roseus (L.) G. don callus responses on dark and chitosan treatments - Sulaiman, Nur Amani Azwa (2015)
Catharanthus roseus (L.) G. Don or periwinkle which originates from Madagascar belongs to the family Apocynaceae. The species has been thoroughly investigated to have alkaloids routinely used in the treatment of various cancer diseases. The present study was conducted to observe the effect of various concentrations of chitosan in the dark on callus growth and development. Callus of C. roseus was used as explants. The callus which was initially initiated on Murashige and Skoog medium was cultured on same medium supplemented with various levels of chitosan (0, 1, 2, 3, 4, 5 mg/L). The experiment was conducted in a Complete Randomized Design (CRD) with 3 replications. Callus growth and development under dark treatment were monitored for a duration of 8 weeks. The main objective of the study was to observe responses on growth and development of callus of C. roseus on chitosan treatments. Data recorded that 3 mg/L chitosan gave the highest mean dry weight 0.28 g while the lowest was 0.17 g from 4 mg/L treatment. The control gave the highest level of boron of 0.18% while in 5 mg/L treatment gave the lowest level of 0.05%. The study concludes that callus growth decreases on medium supplemented with chitosan. Dark treatment did not give positive responses to chitosan supplementation.